Evaluation of the ethical conduct of the Seropédica-RJ community when buying products without a seller (Research, Society and Development, 2021)
The spread of the idea that acts of corruption are daily and acceptable in Brazil, brought a negative image of our society. In recent years, on a professional level, the ethical and moral values of professional conduct have been collected in addition to technical knowledge. Thus, initiating ethics projects is important to bring the discussion a current topic, little disseminated and very controversial to students of higher education. The present work is the result of two years of research developed by the PET-Floresta group in the years 2017 and 2018. The main idea of the project was to test the honesty of the academic community and surroundings of UFFRJ through the sale of products without the presence of a formal seller on the spot. We verified that the project attracted the attention of 670 people and obtained only 1% of crimes. This result proved that corruption is not something common among the attitudes of the community studied.